THE UNIQUENESS OF THE WARUNGBOTO HERITAGE SITE AS AN INTERESTING SELFIES PLACE IN YOGYAKARTA - Isdarmanto Isdarmanto; Christantius Dwiatmaja; John J.O.I Ihalauw; Hari Sunarto; Antonius Suryo Abdi (Pringgitan, 2020)
The development of tourism in various regions in Indonesia has been able to encourage all aspects of people's lives, to be able to work, to fill the opportunities and challenges of globalization in information technology that has been running very fast now. In its development, tourism excellence from the aspect of local wisdom, especially natural resource assets, culture, history, has become the main attraction of tourism destinations of special interest today. Warungboto historical building site is one of the historical tourism assets of Sri Sultan Hamengku Buwono II, which has an exotic and unique value that is widely used by millennial teenagers to take selfie. So it is very strategic role in promoting Warungboto site in Yogyakarta city branding. The existence of Warungboto site as a cultural preservation and provides more information about the history of the royal family of the Palace of Jogjakarta in the era of Sri Sultan Hamengkubuwono II. This study uses qualitative research so that it can be more in-depth and able to increase the philosophical value of the history of Warungboto site more broadly in the competitive aspects of Yogyakarta Tourism marketing in the millennium era.Keywords: warungboto site, philosophical value, jogja’s branding